2017
DOI: 10.1016/j.amsu.2017.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Cost and morbidity analysis of chest port insertion in adults: Outpatient clinic versus operating room placement

Abstract: BackgroundTotally implantable venous access devices (TIVADs) represent a convenient way for the administration of medications or nutrients. Traditionally, chest ports have been positioned by surgeons in the operating room, however there has been a transition over the years to port insertion by interventional radiologists in the radiology suite. The optimal method for chest port placement is still under debate.Materials and methodsData on all adult patients undergoing isolated chest port placement at our instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
1
10
0
2
Order By: Relevance
“…Furthermore, Feo et al [17] investigated the costefficiency of chest port placements when performed in the operation room or the outpatient clinic. They reported that the average cost for chest port placement was significantly higher when performed in the operation room compared to the outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Feo et al [17] investigated the costefficiency of chest port placements when performed in the operation room or the outpatient clinic. They reported that the average cost for chest port placement was significantly higher when performed in the operation room compared to the outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Previous studies regarding the TIVAD insertion are summarized in Table 4. According to the existing Guth [5] Yildizeli et al [6] Araújo et al [7] Narducci et al [8] Keum et al [9] Seok et al [10] Nagasawa et al [11] Aziret et al [12] An et al [13] Gurkan et al [14] Ma et al [15] Zerati et al [16] Feo et al [17] Bazine et al [18] Yanık et al [19] 2018 3000 SV, IJV Kim et al [20] literature, the overall complication rate following TIVAD insertion ranges from 3.1 to 33.9%. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The overall complication rate in our study population was 12.5%, consistent with the results reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to the large case series, the rate of catheter mispositioning following TIVAP insertion varies between 0.2% and 3.1% [2,[7][8][9][10][11][12][13][14][15][16][17] (Table 1). [16] 2018 3000 0.2% 9.6% Kim et al [17] 2019 843 0.3% 4%…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that TIVAP insertion under imaging guidance reduces the procedure-related complication rates [18][19][20]. On the other hand, surgeons use either cut-down or percutaneous landmark-based technique for implantation, with low complication rates [2,[7][8][9][10][11][12][13][14][15][16][17]. Since we, the surgeons, are very familiar with blind-landmark technique as well as vascular anatomy of neck and chest regions, and also may recognize and treat the potential procedure-related complications quickly and properly, we applied the blindlandmark technique during TIVAP insertion but unfortunately observed this adverse event.…”
Section: Discussionmentioning
confidence: 99%